Efektivitas Media Sosial sebagai Sarana Promosi Pelatihan Project Management AGAVI Institute dengan Pendekatan AIDA - Aini, Azizah; Yudha, Eka Purna (Universitas Galuh, 2025)
One of the education in the agricultural sector whose information can be found on Instagram social media, is Project Management through virtual agribusiness training. This study aims to (1) Identify the characteristics of consumers of the AGAVI Institute Project Management Training Program (2) Analyze the effectiveness of promotional media on consumer buying interest in the This study analyzes the effectiveness of social media using the AIDA approach observatively and exploratively through a qualitative approach, determining informants and respondents purposively, namely Project Management training users and 2 informants (Program & Relation Manager) AGAVI Institute. Proving the AIDA approach is considered effective with an overall score of 4.08 and the score of each AIDA variable is worth attention 4.25, interest 4.10, desire 4.02, and action 3.97. The evaluation that can be done by AGAVI Institute after this research is to pay attention to promotional content so that it can convince the audience to purchase the training offered.